ANALISIS FRAMING GERAKAN SOSIAL AKSI CEPAT TANGGAP (ACT) DI MEDIA SOSIAL - Derry Ahmad Rizal; Muhsin Nurhalim; M. Putra Yuniar Avicenna; Hosnor Rofiq (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2022)
As a humanitarian agency, Aksi Cepat Tanggap (ACT) utilizes social media to promote its activities as well as invite the audience to be involved by donating or volunteering. This research focuses on the social media content displayed so that the public can help each other. By using qualitative descriptive methods and using Norman Fairclough's theory of Critical Discourse Analysis, the results of this study suggest that the display of text, images, and discourses narrated by Aksi Cepat Tanggap (ACT) on social media is filled with experiential values, relational values, expressive values, and collective values ​​with strong Islamic nuances. The public's interpretation of texts and images is also reflected in the largest source of donations i.e. from the public.